Contribution to the knowledge of the African entomical biodiversity. III. – Oedichirus georgesi n. sp.from Sao Tomé & Principe (Coleoptera, Staphylinidae, Paederinae). - (:unkn) unknown (My University, 2023)
Oedichirus georgesi n. sp. (Staphylinidae, Paederinae) is described from Sao Tomé & Principe. It differs from the Oedichirus known to date by the shape of its aedeagus and by a series of characteristics of the head, pronotum and Sternum VIII.
Keywords: African Research